Pemanfaatan Aplikasi Mathway dalam Menyelesaikan Soal Kalkulus pada Mahasiswa Tadris Matematika - Khaeril Muttaqin, Andi; Yahya, Yusriman; Irmayanti (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The aim of this study was to describe the use of mathway applications in solving calculus problems for Tadris Mathematics students at the Muhammadiyah Islamic Institute of Religion. The type of research used in this research is descriptive research with a qualitative approach. The collection of data used is a test, interviews. The data analysis technique used is data collection, data presentation, data analysis and drawing conclusions. The results of this study are the application of Mathway as an alternative in solving calculus problems which are considered difficult by students. The findings of this study indicate that the Mathway application can be used by anyone at any time to facilitate learning activities and to become a learning media tool, especially in solving math problems. This application can make it easier for students to solve problems because in addition to the final result, it can also be used to see the process of solving the problem.